1978
DOI: 10.1530/jrf.0.0530045
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of testosterone 5 -reductase activity and growth of accessory sex tissues in castrated male mice

Abstract: The steroid 4-androsten-3-one-17beta-carboxylic acid (17betaC) reduced the growth-promoting actions of testosterone, but not those of DHT in accessory sex tissues of castrated mice. The 5alpha-reduction of testosterone to DHT in these tissues was also reduced by 17betaC treatment, suggesting that DHT formation is a required step in the mechanism of action of testosterone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Testosterone propionate, but not DHTP, stimulation of seminal vesicle and ventral prostate gland weight was prevented by simultaneous treatment with 17/3C. This finding is in agreement with similar reports of 17/3C action in CD-I mice (Luttge et al, 1977) and rats (Bradshaw,Awh,& Baum,Note 1). Moreover, deficits in T activation of mating behavior in castrated male rats produced by the administration of the antiandrogen flutamide were also associated with a decline in genital tissue weight (Gladue & Clemens, 1980;Gray, 1977).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Testosterone propionate, but not DHTP, stimulation of seminal vesicle and ventral prostate gland weight was prevented by simultaneous treatment with 17/3C. This finding is in agreement with similar reports of 17/3C action in CD-I mice (Luttge et al, 1977) and rats (Bradshaw,Awh,& Baum,Note 1). Moreover, deficits in T activation of mating behavior in castrated male rats produced by the administration of the antiandrogen flutamide were also associated with a decline in genital tissue weight (Gladue & Clemens, 1980;Gray, 1977).…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that despite 5a-reductase inhibition there should still be T available to interact with androgen receptors and stimulate male sexual behavior. Luttge et al (1977) reported that 17/3C pretreatment of castrated CD-I mice receiving [ 3 H]T caused a reduction in [ 3 H]DHT and an increase in [ 3 H]T recovered from genital tissues. It is not yet known whether 17/3C has a similar effect on the concentration of T and DHT by cells in the central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation